Pelatihan Inovasi Produk Pangan Abon Pepaya Muda di Dusun Pamagersari Desa Tanjungsari Sumedang - Ana Widiana; Tri Cahyanto; Ateng Supriyatna; Astuti Kusumorini; Anggita Rahmi Hafsari; Yani Suryani; Ucu Julita; Ida Kinasih; Mohamad Agus Salim; Risda Arba Ulfa; Ayuni Adawiyah; Isma Dwi Kurniawan; Rahmat Taufik MA; Yuni Kulsum; Adisty Virakawugi Darniwa (JPM PAMBUDI, 2019)
Papaya is a familiar fruit in Indonesia. During this time, papaya fruit is consumed by direct eating and sold at low prices. Young papaya can be processed into a form of creative food products such as abon. The manufacturing process includes preparation of material tools, stripping, steaming for 40 minutes, thin slicing, addition of complementary spices, drying, frying, and serving. The implementation of PKM activities included the dissemination of material and the practice of making abon papaya. Based on the results of the activity, it was obtained information that the participants in the activity didn’t know much about the nutrients contained in papaya fruit, even the participants had never known that papaya fruit could be processed into shredded fruit. The community service activities on the topic of making shredded papaya fruit can increase awareness, knowledge, skills, and also the motivation of the business of Pamagersari Hamlet Community in Tanjungsari Village, Sumedang.